The effect of perceived ease of use, perceived usefulness, and perceived risk on reuse intention mobile banking service - Aurelifa Annisa Friolinda; Yunia Wardi (Universitas Negeri Padang, 2023)
This study aims to analyze the effect of Perceived ease of use, Perceived usefulness, and perceived risk on Reuse intention of mobile banking services with Trust as mediation for Bank Nagari customers in Padang City in the new normal phase. In this study, 160 respondents comprised the sample size. The distribution of online questionnaires was used for data capture, and the SmartPLS program was used for data processing. According to the findings of this study (1) Trust has a positive and significant effect on mobile banking reuse intentions. (2) Perceived convenience of use has a positive and insignificant effect on trust. (3) Perceived efficacy has a positive and significant effect on trust. (4) Perceived risk has a positive and significant effect on trust. (5) Perceived convenience of use has a positive and insignificant effect on the intention to utilize mobile banking services mediated by trust. (6) Perceived efficacy has a positive and significant effect on the intention to utilize mobile banking services, as mediated by trust. (7) Perceived risk has a significant positive effect on the reuse intention of mobile banking, which is mediated by trust. (8) The perceived usability of mobile banking has a positive and significant influence on the likelihood of future use. (9) The perceived utility of mobile banking has a positive and significant effect on its reuse intention (10) Perceived risk has a positive and insignificant effect on Reuse intention